2019
DOI: 10.1093/ehjci/jez095
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of global, left ventricular myocardial work efficiency before cardiac resynchronization therapy

Abstract: Aims Cardiac resynchronization therapy (CRT) restores mechanical efficiency to the failing left ventricular (LV) by resynchronization of contraction. Global, LV myocardial work efficiency (GLVMWE) can be quantified non-invasively with echocardiography. The prognostic implication of GLVMWE remains unexplored, and we therefore related GLVMWE before CRT to long-term prognosis. Methods and results Data were analysed from an ongoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 20 publications
1
37
0
4
Order By: Relevance
“…In addition, the same authors observed an independent relationship between GCW and occurrence of cardiac death during follow-up but found no independent relationship between GWW and occurrence of cardiac death. 15 Van der Bijl et al 17 found an independent relationship between global LV wasted work ratio and mortality during follow-up in 153 patients receiving CRT. We observed here a strong relationship between preprocedural GWW, CRT response and mortality.…”
Section: Clinical Impact Of Wasted Work In Crt Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the same authors observed an independent relationship between GCW and occurrence of cardiac death during follow-up but found no independent relationship between GWW and occurrence of cardiac death. 15 Van der Bijl et al 17 found an independent relationship between global LV wasted work ratio and mortality during follow-up in 153 patients receiving CRT. We observed here a strong relationship between preprocedural GWW, CRT response and mortality.…”
Section: Clinical Impact Of Wasted Work In Crt Recipientsmentioning
confidence: 99%
“…[10][11][12][13] Although previous studies have reported the relationship between myocardial work indices including global wasted work (GWW) and CRT response, [14][15][16] the link between GWW and outcome has seldom been studied, and divergent results have been noted. 15,17 Therefore, we aimed in the present study to evaluate the relationship among myocardial work indices obtained by PSLs and particularly GWW, response to CRT, and long-term mortality during follow-up in a large cohort of patients receiving CRT in clinical practice.…”
mentioning
confidence: 99%
“…В исследовании P. van der Bijl и соавт. (2019) изначально менее эффективная работа ЛЖ (GWE <75 %) перед выполнением РТ независимо ассоциировалась со сниженным ОБЗОРЫ § риском смерти от всех причин (ОР 0,48 при 95 % ДИ от 0,25 до 0,92; p=0,027) [27]. Таким образом, было доказано, что РТ показывает лучший результат в долгосрочной перспективе, если значительно повышает эффективность работы миокарда.…”
Section: методика оценки работы миокарда лжunclassified
“…установили, что пациенты с артериальной гипертензией имели статистически значимо более низкий GWI ЛЖ по сравнению с контрольной группой при нормальных значениях ФВ и GLS [16]. В ряде исследований показатели миокардиальной работы являлись дополнительными важными критериями отбора и контроля при проведении СRT [38][39][40]. K. Russel и соавт.…”
Section: миокардиальная работа (мYocardial Work)unclassified